U.S.-PLO dialogue : secret diplomacy and conflict resolution - Rabīʻ, Muḥammad, 1940- (University Press of Florida, 1995)
In December 1988 the United States announced its decision to start a dialogue with the Palestine Liberation Organization. A year and a half later, it suspended the dialogue. In the months between, two men with no government ties, Mohamed Rabie and William Quandt, were catalysts in the short-lived talks. This memoir explains in detail their efforts to persuade both the United States and the PLO to focus on "shared" objectives, the difficulties encountered by all sides, and the disappointment they experienced as the talks were suspended. Rabie also discusses the developments that led to the U.S.-PLO dialogue and the activities that made it a reality, offering insights into the decision-making process within the PLO as well as an analysis of prominent PLO personalities